O mito e o maravilhoso na literatura infantil de Alina Paim - Santos, Aline Suelen (2012)
This study proposes a mythical-symbolic reading on three children narratives O lenço encantado (1962), A casa da coruja verde (1962) e Luzbela vestida de cigana (1963), by Alina Paim, based on myth and fantastic present in children‟s books. To do so, it is grounded in literary criticism toward the children‟s and youth‟s literature held by Regina Zilberman (2005) and Tzvetan Todorov (2010), in order to show the importance of this type of literature on ethical education of the child, as well as the anthropology of the imaginary defended by Gilbert Durand (1989) and the myth criticism of Elieser Mielietinski (2002), aiming at emphasizing the presence of some archetypal images in the process of the child´s imagination created by the author, considering the account of myths and symbols that are taken during the human being´s quest for identity and Knowledge.